2009
DOI: 10.1002/chem.200900679
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, and Bonding of Novel Homodinuclear Cobalt and Nickel Borylene Complexes

Abstract: Herein we report for the first time full details on the synthesis and structural characterization of novel homodinuclear bridging cobalt and nickel borylene complexes containing bridging carbonyl ligands, an unusual coordination motif rarely before observed for homodinuclear borylene complexes. Furthermore, the homodinuclear nickel complex represents the first instance of a nickel borylene complex. Quantum chemical analyses of charge-density topology, electron localization function (ELF) and natural charges in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 71 publications
1
9
0
Order By: Relevance
“…Calculations based on the quantum theory of atoms in molecules (QTAIM) and on the electron‐localization function (ELF) revealed that the calculated bonding situation—that is, borylene versus boranediyl—strongly depends on the choice of exchange‐correlation functional . Similar calculations on homodinuclear nickel ( II ) and cobalt ( III ) μ ‐borylene complexes suggested that the dinickel complex should be described as a true bridging borylene whereas bonding in the dicobalt complex is closer to the boranediyl model, irrespective of the choice of density functional . Additionally, complexes I – III are all stabilized by delocalization of the metal–metal bonding molecular orbital over the empty orbitals of the boron bridge and thus fulfil the 18 valence electron rule.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Calculations based on the quantum theory of atoms in molecules (QTAIM) and on the electron‐localization function (ELF) revealed that the calculated bonding situation—that is, borylene versus boranediyl—strongly depends on the choice of exchange‐correlation functional . Similar calculations on homodinuclear nickel ( II ) and cobalt ( III ) μ ‐borylene complexes suggested that the dinickel complex should be described as a true bridging borylene whereas bonding in the dicobalt complex is closer to the boranediyl model, irrespective of the choice of density functional . Additionally, complexes I – III are all stabilized by delocalization of the metal–metal bonding molecular orbital over the empty orbitals of the boron bridge and thus fulfil the 18 valence electron rule.…”
Section: Figurementioning
confidence: 99%
“…[5] Similarc alculations on homodinuclear nickel (II)a nd cobalt (III) m-borylenec omplexes suggested that the dinickel complex shouldb ed escribed as at rue bridging borylene whereasb onding in the dicobalt complex is closer to the boranediylm odel,i rrespective of the choice of density functional. [7] Additionally,c omplexes I-III are all stabilized by delocalization of the metal-metal bonding molecular orbital over the empty orbitals of the boron bridgea nd thusf ulfil the 18 valencee lectron rule.…”
mentioning
confidence: 99%
“…The molecular structure of 3 (Figure ) reveals that it is a terminal hydroborylene nickel complex, with a HB: moiety coordinated by two NHC ligands which have migrated from nickel. As such, 3 is the first example of any metal complex containing a terminal :BH ligand . Notably, the Ni II center of 3 adopts a highly distorted trigonal‐planar geometry (∡(Cl‐Ni‐Si)=149.80(7)°, ∡(B‐Ni‐Si)=78.21(7) o ), due to attractive interactions between the silyl and borylene moieties (d(Si⋅⋅⋅B)=2.624(2) Å; sum of van der Waal's radii=3.90 Å).…”
Section: Figurementioning
confidence: 99%
“…For carbene (or analogous borylene) bridges, the number of attractors is known to depend sensitively on details of the actual bonding situation 53. 57…”
Section: Resultsmentioning
confidence: 99%